Twenty-Five Years of Death: A Report of the Cornell Death Penalty Project on the Modern Era of Capital Punishment in South Carolina - Blume, John H. (2002)
In 1972, the United States Supreme Court determined that the death penalty, as then administered in this country, violated the Eighth Amendment's prohibition against cruel and unusual punishment. Many states, including South Carolina, scurried to enact new, improved capital punishment statutes which would satisfy the Supreme Court's rather vague mandate. In 1976, the High Court approved some of the new laws, and the American death penalty was back in business. After a wrong turn or two, including a statutory scheme which did not pass constitutional muster, the South Carolina General Assembly passed the current death penalty statute in 1977. The first death sentences under the new capital sentencing regime were imposed on October 7 of the same year. With twenty-five years of experience under the South Carolina death belt, an examination of how the new, improved death penalty statute is working is in order. It is time for a report card. The time is right to examine South Carolina's capital punishment scheme not only due to the new regime's twenty-fifth anniversary, but also because of several recent national studies raising troublesome findings about the administration of the death penalty in the United States. For example, Professor James Liebman and his colleagues, in their Broken System studies, found high rates of error in capital cases, as well as racial inequities, geographical disparities, and other systemic defects in the administration of the death penalty. This Study, with its focus on South Carolina, is much more modest. It is an attempt to scrutinize one state's new death penalty from a variety of perspectives in light of these national findings. Thus, after first discussing the legal landscape against which the current capital punishment statute was enacted, this Article will explore who has been sentenced to death in this state; how jurors, the South Carolina Supreme Court, other reviewing courts, and South Carolina's governors have performed their various functions in the system; and how the system stacks up against the promise of a new and improved death penalty. Furthermore, the Capital Jury Project is briefly discussed